Thermoresponsive Electrolytes for Safe Lithium‐Metal Batteries - Jiang, Feng‐Ni; Cheng, Xin‐Bing; Yang, Shi‐Jie; Xie, Jin; Yuan, Hong; Liu, Lei; Huang, Jia‐Qi; Zhang, Qiang (Advanced materials (Weinheim), 2023)
Exploring advanced strategies in alleviating the thermal runaway of lithium‐metal batteries (LMBs) is critically essential. Herein, a novel electrolyte system with thermoresponsive characteristics is designed to largely enhance the thermal safety of 1.0 Ah LMBs. Specifically, vinyl carbonate (VC) with azodiisobutyronitrile is introduced as a thermoresponsive solvent to boost the thermal stability of both the solid electrolyte interphase (SEI) and electrolyte. First, abundant poly(VC) is formed in SEI with thermoresponsive electrolyte, which is more thermally stable against lithium hexafluorophosphate compared to the inorganic components widely acquired in routine electrolyte. This increases the critical temperature for thermal safety (the beginning temperature of obvious self‐heating) from 71.5 to 137.4 °C. The remained VC solvents can be polymerized into poly(VC) as the battery temperature abnormally increases. The poly(VC) can not only afford as a barrier to prevent the direct contact between electrodes, but also immobilize the free liquid solvents, thereby reducing the exothermic reactions between electrodes and electrolytes. Consequently, the internal‐short‐circuit temperature and “ignition point” temperature (the starting temperature of thermal runaway) of LMBs are largely increased from 126.3 and 100.3 °C to 176.5 and 203.6 °C. This work provides novel insights for pursuing thermally stable LMBs with the addition of various thermoresponsive solvents in commercial electrolytes. A thermoresponsive electrolyte is introduced into a working cell to relieve the exothermic reactions between electrodes and electrolytes, the internal short circuit. The critical temperature for thermal safety, “ignition point” of battery, and internal‐short‐circuit temperature of batteries with thermoresponsive electrolyte increase from 71.5, 100.3, and 126.3 °C to 137.4, 203.6, and 176.5 °C compared with routine electrolyte.